On a test statistic connected with the multivariate Behrens - Fisher problem - Gupta, A.; Nagar, D. (Revista Técnica da Faculdade de Engenharia da de Zulia)
The exact null distribution of a test statistic proponed earlier for testing equality to two mean vectors under the intraclass correlation models has been derived in terms of generalized hypergeometric function as well as in series form suitable for computation. Explicit expressions of the density are given for p = 2, 3, 4 and 5.